Peculiarities of plant-based meat substitutes classification in the course of forensic commodity examination - L. Yu. Ulybina; M. V. Harbuz (Bulletin of Kharkiv National University of Internal Affairs)
The article deals with the peculiarities of classification of plant-based meat substitutes in the course of forensic commodity examination. The main attention is paid to determining the authenticity, quality and compliance of these products with regulatory requirements. The examination involves a sequence of studies, including composition analysis, identification of sources of protein components, assessment of textural and organoleptic characteristics, as well as identification of possible impurities and contaminants. These studies are aimed at ensuring the quality and safety of plant-based meat substitutes, which is important for consumer protection and product confidence. The methods of examination, including the use of gas and liquid chromatography, Fourier transform infrared spectroscopy, and solid-phase microextraction, are systematised. The article describes microbiological methods of analysis that allow assessing the microbiological safety of products and identifying the risks of their consumption. Particular attention is paid to the types of defects in plant-based meat substitutes that can occur due to process violations, improper storage or transportation conditions. The most common defects include the presence of mould, changes in texture, smell, taste, and signs of spoilage caused by fat oxidation or contamination with foreign substances. The article describes the sequence of actions performed during the examination: from the initial inspection of the sample, including visual assessment, analysis of texture, colour, smell, and ending with the comparison of the results with the established quality standards. The results of the study are of practical value for expert organisations, manufacturers and consumers. The material presented here contributes to the expansion of the methodological basis of forensic commodity expertise and the formation of criteria for evaluating innovative products.